Critical analysis of the movie Bikini Open. - Aportadera, Ela Vanessa; Azarcon, Rydylyne
This study entitled "A Critical Analysis of the Movie Bikini Open," will find out whether the said film affirms the real state of Philippine Mass Media. The study aims to identify the issues on Philippine media depicted in the movie, point out of the issues confronting media in the Philippine society, determine the similarities and differences of the issues depicted in the movie withe the current state of Philippine media and society, analyze the issues reflected in the movie in the context of Philippine media and society, and point out the implications of the movie on the Philippine media and society., Twelve professionals from Iloilo City coming from the academe, television, radio and print media and the film's director served as respondents of the study. The study used Critical Theories of Communication in analyzing the film in the context of Philippine media and society. Results of the study indicate that Philippine media tends to serve the interest of the dominating class such as advertisers and media owners who exercise power over those below them in their pursuit of economic interests. Philippine mass media is leaning towards the practice wherein corporate responsibility takes over social responsibility. With competition, the media resorted to sensationalism and exploitation.